Comprehensive Study of the Gas Volume and Composition Produced by Different 3–230 Ah Lithium Iron Phosphate (LFP) Cells Failed Using External Heat, Overcharge and Nail Penetration Under Air and Inert Atmospheres - Gemma E. Howard; Jonathan E. H. Buston; Jason Gill; Steven L. Goddard; Jack W. Mellor; Philip A. P. Reeve (Batteries, 2025)
This paper reports on the failure of cells with lithium iron phosphate (LFP) chemistry tested under a range of conditions to understand their effect on the volume and composition of gas generated. Cells of the following formats, 26,650, pouch, and prismatic, and capacities ranging from 3 to 230 Ah, were subjected to external heat, overcharge, and nail penetration tests. Gas volume was calculated, and the following gases analysed: H2, CO2, CO, CH4, C2H4, C2H6, C3H6, and C3H8. Cells that failed via external heating under inert conditions (N2 or Ar atmosphere) at 100% state of charge (SoC) typically generated 0.7 L/Ah of gas; overcharged cells, 0.11–0.68 L/Ah; and nail penetration between 0.3 and 0.5 L/Ah. In general, for all test configurations, regardless of atmosphere, the total gas volume contained a 40% concentration of H2, 15% of CO2, and the remaining gas consisted of varying concentrations of CO and flammable hydrocarbons. This demonstrates that despite differences in gas volume, the failure gas composition of LFP cells remains similar.